Efficacy and safety of 15 mA transcranial alternating current stimulation (tACS) in the therapy of treatment-resistant depression with increased inflammatory activity: Study protocol for a randomized, double-blind, sham-controlled trial - Xuguang An; Jin Zhang; Xiaofei Hou; Chenghao Yang (PLOS One, 2026)
Background and Objectives Treatment-resistant depression (TRD) poses a significant clinical challenge, with traditional antidepressant therapies often ineffective. Elevated peripheral inflammation has emerged as a potential biological subtype of TRD, highlighting the need for novel treatments. Transcranial alternating current stimulation (tACS) has garnered attention for its potential antidepressant effects, particularly through its impact on glial cells, which are involved in neuroinflammation and neuronal interactions. This study aims to assess the efficacy and safety of high-intensity (15 mA) tACS in TRD patients with elevated inflammatory activity. Methods This randomized, double-blind, sham-controlled trial will recruit 70 participants based on C-reactive protein levels (0.85–10 mg/L) and Dutch Method for Staging Therapy-Resistant Depression scores (DM-TRD, > 12.5). The study involves a 4-week tACS/sham intervention followed by an 8-week follow-up. The primary endpoint includes changes in the Montgomery-Åsberg Depression Rating Scale (MADRS) scores from baseline to week 4. Secondary endpoints include MADRS scores at week 2, Self-rating depression and anxiety scale scores, response and remission rates, and the presence of epileptiform activity. It will explore the association between changes in MADRS scores and alterations in EEG parameters and/or concentrations of peripheral biomarkers. Safety assessments will monitor adverse events, vital signs, and ECG parameters, with serious adverse events defined by specific medical conditions. Discussion Understanding the contribution of inflammatory processes to the heterogeneity of depression may provide important insights into its underlying pathophysiological mechanisms and facilitate the identification of novel, mechanism-based therapeutic targets. In this context, the present study aims to explore the potential for the development of more effective, personalized treatment strategies tailored to depressive patients. Trial registration At ClinicalTrials.gov ( NCT06812923 ) on 02 February 2025. Protocol version : 15mA tACS 1.0